THE IMPLEMENTATION OF FACILITY AND INFRASTRUCTURE MANAGEMENT OF ELEMENTARY SCHOOL IN MALANG CITY, INDONESIA - Taufiq Akbar Alfajri; Trisna Andarwulan (Erudio Journal of Educational Innovation, 2021)
The importance of educational facilities and infrastructure is so important that every educational institution is competing to meet the standard criteria for facilities and infrastructure in order to improve the quality of the learning process to support the success of learning objectives in schools. Educational facilities are all facilities that aim to facilitate direct educational activities and learning processes such as the availability of blackboards, textbooks, educational teaching aids. In contrast to educational infrastructure, which has almost the same characteristics as educational facilities, namely to facilitate educational activities and the learning process but is not direct, such as buildings, classrooms, tables, chairs, access to schools. Educational facilities and infrastructure are basically grouped into four groups consisting of land, buildings, equipment, and school furniture. This research used quantitative descriptive with 250 teachers as the research subject to measure the implementation of facilities and infrastructure management in Malang City. Based on the results of measurements of planning stage it is known that there are 22.4% respondents stated that unsatisfied, 50% respondents stated that planning is unsatisfied, 24% respondents stay neutral, 3.2% respondent satisfied and 0.4% respondents stated they feel very satisfied. While in using stage, it is known that 24% respondents stated that they are unsatisfied, 71.6% respondents stated neutral, and 4.4% respondents stated that they are satisfied. Meanwhile in inventorying, it was found that 67.6% respondents stated that they were neutral, 28.8% were satisfied, and 3.6% were very satisfied. Next stage is maintaining, it is known that 20.4% of teachers are unsatisfied and 79.6% of teachers are satisfied. The last stage is deleting, it was known that 0.4% of teachers are very unsatisfied, 40.4% stated that they find unsatisfied, 54% of teachers stated they are neutral, and 5.2% of teachers are satisfied.